Politik hukum revisi undang-undang KPK yang melemahkan pemberantasan korupsi - Yulianto, Yulianto (Jurnal Cakrawala Hukum, 2020)
This writing discusses the substance of the revision of law number 30/2002 about commission for the eradication of corruption (KPK). The problem that occurs is that the revision of the law actually weakens the KPK and sides with criminal acts of corruption. This paper aims to understand and understand about how the provisions of the revision of the KPK law are actually out of their noble objectives as a political political choice that will strengthen the eradication of corruption in Indonesia. The author uses the normative legal research method with the analysis approach to the legislation and the ruling of the constitutional court. This paper produces research that the KPK should be strengthened by presenting revisions to the law in favor of improving performance and not on things that actually appear to weaken the KPK. How to cite item:Â Yulianto, Y. (2020). Politik hukum revisi undang-undang KPK yang melemahkan pemberantasan korupsi.Â Jurnal Cakrawala Hukum, 11(1), 111-124. doi:https://doi.org/10.26905/idjch.v11i1.4049